IMPLEMENTASI CONVENTION OF THE RIGHTS OF THE CHILD DALAM PEMENUHAN HAK PENDIDIKAN BAGI PENGUNGSI ANAK- ANAK DI KOTA PEKANBARU TAHUN 2019-2021 - Maria Ulfa; Yusnarida Eka Nizmi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This research focuses on analyzing the implementation of the Convention of the Rights of the Child (CRC) to fulfill the right to education for refugee children in the city of Pekanbaru for three years. The primary analysis of this research highlights the role of the Indonesian state as a party to the CRC and collaboration of various local and international actors in formal and informal education. Along with this, the writing of this thesis uses qualitative research methods with a combination of primary data references (interviews with UNHCR, IOM, refugees, Kesbangpol, schools and official document analysis) and secondary (analyses of journals, theses, books, websites, and periodic reports. Meanwhile, the discussion of this research uses the International Organization theory as an analytical tool. Keywords: Convention of the Rights of the Child, Right to education, Refugee children